THE CORRELATION OF LEVEL UNDERSTANDING OF MALE ROLE AS A HEAD FAMILY WITH RESPONSIBILITY IN BUILDING A HAPPY FAMILY - Tri Wahyuni; Adelina Hasyim; Hermi Yanzi (FKIP Unila, 2012)
The aim of the research described the correlation of level understanding male role as the family head with the responsibility in building a happy family in Cipadang, Gedong Tataan, Pesawaran. The method of the research used descriptive-quantitative method. The sample of the research was 20 respondents. The analysis of the data used Chi quadrates. The technique of collecting data used questionnaire. The result of the research showed that: (1) The understanding of male role as a family head (X) dominant enough role, with the presentation of 36%, (2) the responsibility of the family head in building a happy family dominant enough responsibility 48% (3) the result of the research showed the positive correlation, significant, and the category of higher close between male role as a head of household with the responsibility in building a happy family. So, the higher level of understanding male role as the family head, the better are the attitude of responsibility in building a happy family.Keywords: male role as a family head, the responsibility as head of the family, happy family.